Detection and identification of O‐GlcNAcylated proteins by proteomic approaches. Issue 5 (3rd February 2015) - Vercoutter‐Edouart, Anne‐Sophie; Yazidi‐Belkoura, Ikram El; Guinez, Céline; Baldini, Steffi; Leturcq, Maïté; Mortuaire, Marlène; Mir, Anne‐Marie; Steenackers, Agata; Dehennaut, Vanessa; Pierce, Annick; Lefebvre, Tony
Abstract : O ‐GlcNAcylation ( O ‐linked beta‐N‐acetylglucosaminylation) is a widespread PTM confined within the nuclear, the cytosolic, and the mitochondrial compartments of eukaryotes. Recently, O ‐GlcNAcylation has been also detected in the close vicinity of plasma membranes particularly in lipid microdomains. The detection of this PTM can be easily done if appropriate controls and precautions are taken using a wide variety of tools including lectins, antibodies, or click‐chemistry‐based methods. In contrast, the identification of the proteins bearing O ‐GlcNAc moieties and the localization of the precise sites of O ‐GlcNAcylation remain challenging. This is due to the lability of the glycosidic bond between hydroxyl group of serine or threonine and N ‐acetylglucosamine using conventional fragmentation techniques such as CID. To tentatively overcome this technical limitation, electron‐capture dissociation, or electron‐transfer dissociation MS/MS are now used. Thanks to these breakthroughs, a large number of O ‐GlcNAc sites have been identified to date but these methodologies remain far from being used in routine.